2018
DOI: 10.1111/phn.12560
|View full text |Cite
|
Sign up to set email alerts
|

Simulation as a learning method in public health nurse education

Abstract: Objective: To view simulation as a learning method in the light of learning theories and to describe the student's reflections and experiences of simulating anaphylaxis during vaccination. Design and Sample:Public health nursing students at a university in Norway simulated scenarios related to anaphylaxis during vaccination of an infant. The aim of the intervention was to facilitate the competence of public health nurses to handle unforeseen events associated with vaccinations. The students wrote reflection no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 9 publications
2
23
0
7
Order By: Relevance
“…Qualitative studies of the lived experience of nursing students in simulations reported both positive experiences, such as learning practices without fear, gaining confidence in clinical practicum, maturing in the profession, awareness and understanding, and simulation as preparation for practice [18][19][20][21]; and negative experiences, such as being anxious about having students' mistakes exposed, anxiety from being observed, an uncertain journey to achievement and needing a navigator, and pre-experience anxiety [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies of the lived experience of nursing students in simulations reported both positive experiences, such as learning practices without fear, gaining confidence in clinical practicum, maturing in the profession, awareness and understanding, and simulation as preparation for practice [18][19][20][21]; and negative experiences, such as being anxious about having students' mistakes exposed, anxiety from being observed, an uncertain journey to achievement and needing a navigator, and pre-experience anxiety [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This dilemma creates the necessity to justify why simulation as a learning method provides students with a more realistic approach to solving practical challenges than traditional teaching. When paediatric emergencies occur in the clinic, students are often not first in line to respond and thus do not gain sufficient experience to learn how to deal with these situations [32]. Theories of reflection, such as Schön's reflection theory, describe how students who participate in simulations of clinical situations have the opportunity to make decisions and exercise critical thinking [25].…”
Section: Discussionmentioning
confidence: 99%
“…Det oppleves motiverende for studentene og skaper effektive laeringsmuligheter (Wiesbeck, Bauer, Gartmeier, Kiessling, Møller, Karsten, Fischer & Prenzel, 2017). Annen forskning innen helsefaglige utdanninger viser at simulering brukt som pedagogisk verktøy forbereder studentene til å øve på realistiske situasjoner (Akselbo, Olufsen, Ingebrigtsen & Aune, 2018;Brannan, White & Bezanson, 2008;Breckwoldt, Gruber & Wittman, 2014). Videre viser studier at simulering i sykepleieutdanningen kan erstattes av ferdighetstrening, og at samme laeringsutbytte oppnås i forhold til ferdigheter og kunnskap (Celik, Ceylantekin & Kilic, 2017;Forcina, Woodley & Goodwin, 2018).…”
Section: Innledningunclassified
“…Videre opplever de å bli trygge i eget yrke (Rauen, 2004;Østergaard, 2004). Dette samsvarer med Akselbo et al, (2018) som viser til at sykepleiestudentene opplever at simulering er et realistisk og effektivt laeringsverktøy som er nyttig for praksis og som gir grunnlag for refleksjoner. Derimot viser en studie at ferdighetstrening og simulering gir samme tilegnelse av kunnskap innen identifisering, prioritering og iverksetting av relevante sykepleietiltak (Bratås, Albriktsen, Eriksson & Grønning, 2018).…”
Section: Innledningunclassified
See 1 more Smart Citation